Upaya Guru Pendidikan Agama Islam dan Budi Pekerti dalam Mengembangkan Karakter Religius Siswa Kelas II SD Ahmad Dahlan Kabupaten Sumedang Tahun Ajaran 2019/2020 - Encep Iman Hadi Sunarya; Martini Jamaris; Yetti Supriyati (UM Purwokerto Press, 2022)
The results of this study are as follows: First, the condition of the religious character of second grade students this year is better than the previous year. Second, the effort is to do routine habits, such as: (a) Tadarus Qur'an; (b) Cult; (c) Duha prayer; (d) Prayer together; (e) Zuhur prayer in congregation; and (f) donate. Third, the supporting factors are: (a) Policy from the principal; (b) Support from other teachers (c) Adequate facilities and infrastructure; (d) Students are enthusiastic and enthusiastic; and (e) Good environment. Fourth, the inhibiting factors are: (a) Lack of support from parents; (b) Unfavorable environment; and (c) Limited implementation time. Fifth, the solutions to the inhibiting factors are: (a) PAI teachers and Budi Pekerti always provide direction to parents; (b) Giving awareness to students about the dangers of an unfavorable environment; and (c) Conduct continuous evaluation.